Печатка династії Петрункевичів з архіву М.А.Шліппенбаха (1928–2010) як джерело з історії земського лібералізму північної України (60–80 рр. ХІХ ст.) - Комаровський, Ю.; Котельницький, Н. (Сiверянський лiтопис, 2019)
Розвідка присвячена запровадженню до міжнародного наукового обігу унікального
джерела з історії земського ліберального руху на півночі Лівобережної України – печатки
династії Петрункевичів з архіву М. А. Шліппенбаха. Наведений сфрагістичний опис історичної перлини, опубліковано фото відбитку печатки. Розглянуті ймовірні причини
відсутності офіційно затвердженого або самобутнього фамільного герба Петрункевичів. Акцентовано увагу на важливості історичного джерела для дослідження проблем дворянської генеалогії та геральдики основних представників опозиційного руху. The intelligence is devoted to the introduction into the international scientific circle of a
unique source on the history of the Zemsky liberal movement in the north of the Left Bank
of Ukraine, the seal of the dynasty Petrunkevichs from the archives of M.Shlipenbach. The
statement of the scientific problem about the necessity of searching, forming and studying the
heraldic gallery of members of the Zemsky liberal frontier of northern Ukraine was declared.
The sphygmic description of the historical pearl is given, a photo of a seal of a seal is published.
Probable reasons for the absence of the officially approved or original family coat of arms of
Petrunkevich are considered. In particular, there are two possible circumstances that could have
caused such a state of affairs: the socio-economic crisis of the Petrunkevich dynasty after the
abolition of the slave system in the Russian empire and the specificity of the metamorphosis in
the relations between the Russian monarchy, the titular nobility and the non-Russian aristocracy.
The emphasis is placed on the importance of the historical source for the study of problems of
the nobility genealogy and heraldry of the main representatives of the opposition movement.